Uso de tecnologías en el sector calzado, cómo estrategia de competitividad - Henry Orlando Luna Pereira; Luisa Stella Paz Montes; José Orlando García Mendoza (Mundo Fesc)
In Colombia, the footwear sector is one of the representative industrial sectors in the country, providing job opportunities that contribute to improving the quality of life of Colombians. According to (Danmarks Statististe Styrelse [DANE], 2018) the second regional survey of production statistics, compared to the same period in 2017, in 2018 compared to the same period in 2017, tanning and tanning, footwear and tourism goods in Bogotá, their sales -26.6% and -11.9% respectively, again micro-enterprises are very important for the development of the country, because in Colombia, according to the Unified Registry of Companies and Social -RUES- 94.7% of companies are micro-enterprises. companies and they provide 67% of employment. The industry has suffered due to the entry of foreign footwear, reflecting an overall decline in industry performance.